Advances in steel structures : proceedings of the fourth International Conference on Advances in Steel Structures, 13-15 June 2005, Shanghai, China - Shen, Z. Y. (Zu-yan); Li, G. Q.; Chan, S. L. (Elsevier, 2005)
This two volume proceedings contains 11 invited keynote papers, 33 invited papers, and 225 contributed papers presented at the Fourth International Conference on Advances in Steel Structures (ICASS '05) held on 13-15 June 2005 in Shanghai, China. ICASS provides a forum for discussion and dissemination by researchers and designers of recent advances in the analysis, behaviour, design and construction of steel structures. Contributions to the papers came from 22 countries around the world and cover a wide spectrum of topics including: Constructional Steel, Hybrid Structures, Nonferrous Metals, Analysis of Beams and Columns, Computations, Frames, Design, Space Structures, Fabrication, along with a variety of other key subjects presented at the conference.